Vascular Calcification: An Important Understanding in Nephrology - Zununi Vahed, Sepideh (Vasc Health Risk Manag, 2020)
Vascular calcification (VC) is a life-threatening state in chronic kidney disease (CKD). ﻿High cardiovascular mortality and morbidity of CKD cases may root from medial VC promoted by hyperphosphatemia. Vascular calcification is an active, highly regulated, and complex biological process that is mediated by genetics, epigenetics, dysregulated form of matrix mineral metabolism, hormones, and the activation of cellular signaling pathways. Moreover, gut microbiome as a source of uremic toxins (eg, phosphate, advanced glycation end products and indoxyl-sulfate) can be regarded as a potential contributor to VC in CKD. Here, an update on different cellular and molecular processes involved in VC in CKD is discussed to elucidate the probable therapeutic pathways in the future.